Experimental methodology for turbocompressor in-duct noise evaluation based on beamforming wave decomposition. (18th August 2016) - Torregrosa, A.J.; Broatch, A.; Margot, X.; García-Tíscar, J.
Abstract: An experimental methodology is proposed to assess the noise emission of centrifugal turbocompressors like those of automotive turbochargers. A step-by-step procedure is detailed, starting from the theoretical considerations of sound measurement in flow ducts and examining specific experimental setup guidelines and signal processing routines. Special care is taken regarding some limiting factors that adversely affect the measuring of sound intensity in ducts, namely calibration, sensor placement and frequency ranges and restrictions. In order to provide illustrative examples of the proposed techniques and results, the methodology has been applied to the acoustic evaluation of a small automotive turbocharger in a flow bench. Samples of raw pressure spectra, decomposed pressure waves, calibration results, accurate surge characterization and final compressor noise maps and estimated spectrograms are provided. The analysis of selected frequency bands successfully shows how different, known noise phenomena of particular interest such as mid-frequency "whoosh noise" and low-frequency surge onset are correlated with operating conditions of the turbocharger. Comparison against external inlet orifice intensity measurements shows good correlation and improvement with respect to alternative wave decomposition techniques. Abstract : Graphical abstract: Abstract : Highlights: A novel evaluation methodology for turbocompressors noise emission is presented. Noise emission characterized by measuring sound intensity using wave decomposition. Signal processing yields noise level maps in given frequency bands and spectrograms. Whoosh noise identified by the signal processing extends also far from surge region.